Penerapan Model Pembelajaran Blended Learning Dalam Meningkatkan Kemandirian dan Hasil Belajar Korespondensi - Rina Suryani Harahap (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This study aims to analyze the effectiveness of using learning tools based on the Blended Learning learning model by utilizing online learning applications in increasing student independence and learning outcomes in Correspondence subjects for class X SMK Negeri 1 Kisaran. This research was conducted at SMK Negeri 1 Kisaran, with a population of 72 people. The sample in this study was taken by purposive sampling technique. From the results of the data analysis of the control class, the learning independence score was 3.78 with the